PELAKSANAAN PERJANJIAN KERJA WAKTU TERTENTU TERKAIT PEMBERIAN UPAH PEKERJA MENURUT UNDANG UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DI PT. SAKURA BUMI PERSADA KABUPATEN PELALAWAN - Bisma Al Ibra; Maryati Bachtiar; Riska lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Work has very important significance in human life so that every person in need of work. To obtain a job and a decent living is the right of every citizen, it is already evident in the set in Article 27 Paragraph (2) of the 1945 Constitution, namely: every citizen the right to work and a decent living for humanity. It is not all just hung to the government. Employers also have an important role in employment so that employment can be based on the full wisdom in all sectors. A company is obliged to see to it that the employees have the awareness to be responsible for the smooth progress, the survival of the company. Therefore in need of a labor agreement that connects between a person who acts as a worker or workers with a person who acts as an employer for the creation of a form of relationship that binds to perform an act in accordance with Act No. 13 of 2003 concerning employment.From the above information, the author makes some problem formulation in which the formulation of the problem is how the implementation of the agreements specified time-related wages in PT. Sakura Bumi Persada in Pelalawan Pangkalan Kerinci, what are the factors that hinder the provision of wage workers, how the efforts made by PT. Sakura Bumi Persada in Pelalawan Pangkalan Kerinci in overcoming delays in payment of wages.After this when in Act No. 13 of 2003 has been explained in detail about the rights and obligations of employers and workers, but why there are still many companies that are in default to its employees. Supposedly the company and its employees can be more concerned about their rights and responsibilities in conducting an employment agreement that the company and the workers were not negligent so as to create harmony which resulted in economic communities working in the company and increasing the better.Key Word : Employment Agreement – Company